Input productivity in agriculture on the north coast of Colombia (1971)
The allocation of capital within the agricultural sector 1 of a developing nation is, or should be, of primary concern to those who are formulating or implementing development policy. The critical nature of the use of capital is in large part created by its shortage as an input in the development process, and by the widespread demand and need for capital inputs to escape from what is now commonly called "traditional" agriculture (2, p. 18). A scarcity of capital may present barriers at various levels of potential investment (37, pp. 83-6). At one level is the shortage of investment capability on.the part of a large portion of the agricultural entrepreneurs. This shortage is aggravated by the reluctance to commit substantial portions of available capital to agricultural activities.